Oral Health-Related Quality of Life among an Australian sample of people who inject drugs - Truong, A.; Higgs, Peter; Cogger, S.; Jamieson, L.; Burns, L.; Dietze, P. (Wiley-Blackwell Publishing, Inc., 2014)
Objectives - People who inject drugs (PWID) have poor oral health. However, their oral health-related quality of life (OHRQoL) is unknown. Our study was designed to measure the OHRQoL of PWID. Methods - The Oral Health Impact Profile-14 (OHIP-14) was administered to 794 PWID recruited in Australian capital cities as part of the 2013 Illicit Drug Reporting System (IDRS). Three OHIP-14 summary indicators were examined: “Prevalence” (proportion reporting ≥1 item at least “fairly often”), “severity” (mean total OHIP-14 score), and “extent” (number of impacts reported at least “fairly often”). Associations between “prevalence” and “extent” and variables drawn from the health, drug use, and social domains were investigated. Results - All OHIP-14 summary indicators among IDRS participants were significantly higher than in the general Australian population. In multivariate analysis, the “prevalence” indicator was significantly and positively associated with female gender [adjusted odds ratio (AOR) = 1.75, 95% CI 1.27-2.38], those born in Australia (AOR = 2, 95% CI 1.25-3.23), not completing Year 10 compared with those who had completed Year 12 or a higher qualification (AOR = 1.59, 95% CI 1.03-2.44), and methadone treatment (AOR = 1.61, 95% CI 1.14-2.29). The “extent” indicator was significantly and positively associated with female gender [adjusted incidence rate ratio (AIRR) = 1.56, 95% CI 1.19-2.08], unemployment (AIRR = 1.59, 95% CI 1.01-2.44), and having an injecting career of 10-20 years (AIRR = 1.76, 95% CI 1.03-3.01).